Perilaku Harian Rusa tutul (Axis-axis) di Kawasan Industri Pt Kujang Cikampek Jawa Barat - Salasti Nafi Izlima; Erie Kolya Nasution; Soeminto Soeminto (Fakultas Biologi | Universitas Jenderal Soedirman, 2012)
A study entitled daily spotted deer (Axis-axis) Behavior in the PT Kujang Cikampek Industrial Area of West Java” wa aimed to determine the daily bahaviour and types of vegetation as habitat for spotted deer in PT Kujang Cikampek West Java. The study was conducted by using survey methods, daily behavioural observations were made by the Scan sampling and Time sampling method. The vegetation data were collected by census method. Five individual of the spotted deers in the Industrial Area of PT Kujang Cikampek were captured and classified by age and sex distribution. The result showed the highest activity is performed either in the feeding behavior for the breeding region is 45,67%. While the average breeding area of 1b eating behavior was 46,26%. The pattern of eating behavior the most performed is grazing and the most preferred vegetation is grassland.